Unlocking Indonesia’s 89% Islamic Finance Gap: Data-Driven Communication Strategy from BSI, Muamalat & Malaysia’s VBI Leaders - Hayunaji Hayunaji (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The development of Islamic finance in Indonesia demonstrates significant potential but continues to face challenges caused by the gap between increasing financial literacy and the low level of Islamic financial inclusion among society. This study aims to analyze data-driven communication strategies to bridge the Islamic financial literacy and inclusion gap by examining practices from Bank Syariah Indonesia, Bank Muamalat Indonesia, BTPN Syariah, and Malaysia’s Value-Based Intermediation approach. This research applies a qualitative approach with a comparative case study design using secondary data obtained from regulatory reports, financial institution publications, industry documents, and academic articles published between 2020 and 2025. The findings reveal that improving literacy does not automatically lead to the adoption of Islamic financial services because several barriers remain, including trust, perceived value, accessibility, and communication relevance. The discussion indicates that effective communication strategies require a segmented approach through the integration of digital transformation, community engagement, fintech collaboration, and communication emphasizing social and sustainability values. Malaysia’s Value-Based Intermediation approach demonstrates that impact-oriented communication can strengthen the broader positioning of Islamic finance. This study concludes that accelerating Islamic financial inclusion in Indonesia requires a strategic shift from awareness-based communication toward behavior-oriented communication that emphasizes trust development and value creation.